Detection Of Primary User Emulation Attack in Cognitive Radio Networks Based On TDOA using Grey Wolf Optimizer - Rehman, Aasia (International Journal of Computer Sciences and Engineering, 2019)
Cognitive Radio is a technology that overcomes the problem of spectrum shortage by embedding the wireless devices with an intelligent agent to make the opportunistic use of available white spaces in the radio environment. However due to ubiquitous nature of cognitive radio networks, it is sensitive to a number of security threats which disturbs the overall performance of cognitive radio networks. The main goal of this paper is to thwart one of the security threats in Cognitive Radio Networks known as Primary User Emulation Attack. Primary User Emulation Attack is one of the most popular Dynamic Spectrum Access attack. In this paper we are detecting the primary user emulation attack based on TDOA values using Grey Wolf Optimizer. Simulation results show that Grey Wolf Optimizer is more accurate than using the Particle Swarm Optimization Algorithm for mitigation.